EFEKTIVITAS PEMBELAJARAN: PERAN PENTING STANDAR PENILAIAN - Putu Vina Aryadnyani; I Gusti Agung Ayu Putu Listyana; Ketut Novitayanti; I Made Krisna Bayu; Ni Wayan Rati (STKIP Subang, 2026)
Assessment is a strategic component in education that functions to monitor learning progress and continuously improve the quality of instruction. This study aims to analyze the implementation of educational assessment standards in junior high schools (SMP) by referring to Permendikbudristek Number 21 of 2022, which covers aspects of concepts, principles, procedures, and the use of assessment instruments. The method used in this study is descriptive qualitative with data collection techniques through field observations at SMP Negeri 4 Seririt and SMP Laboratorium Undiksha Singaraja. The results indicate that, in general, educational units have implemented diagnostic, formative, and summative assessments in the fairly good category. However, significant administrative constraints were still found at the planning stage, where approximately 50% of teachers at the observation sites had not yet developed comprehensive assessment tools, specifically in drafting test specifications and item cards. The implementation of this standard has a positive impact on increasing the objectivity and transparency of assessment through the use of rubrics, but on the other hand, it increases the administrative burden on educators. The study concludes that continuous strengthening of teacher competence is required through technical workshops on developing Higher Order Thinking Skills (HOTS) based assessment tools to support a more accountable and high-quality evaluation system.